7w+6y+6x+6x-11y+3w=

Simple and best practice solution for 7w+6y+6x+6x-11y+3w= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7w+6y+6x+6x-11y+3w= equation:


Simplifying
7w + 6y + 6x + 6x + -11y + 3w = 0

Reorder the terms:
7w + 3w + 6x + 6x + 6y + -11y = 0

Combine like terms: 7w + 3w = 10w
10w + 6x + 6x + 6y + -11y = 0

Combine like terms: 6x + 6x = 12x
10w + 12x + 6y + -11y = 0

Combine like terms: 6y + -11y = -5y
10w + 12x + -5y = 0

Solving
10w + 12x + -5y = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-12x' to each side of the equation.
10w + 12x + -12x + -5y = 0 + -12x

Combine like terms: 12x + -12x = 0
10w + 0 + -5y = 0 + -12x
10w + -5y = 0 + -12x
Remove the zero:
10w + -5y = -12x

Add '5y' to each side of the equation.
10w + -5y + 5y = -12x + 5y

Combine like terms: -5y + 5y = 0
10w + 0 = -12x + 5y
10w = -12x + 5y

Divide each side by '10'.
w = -1.2x + 0.5y

Simplifying
w = -1.2x + 0.5y

See similar equations:

| 16x-20=-12x+100 | | 3=2sin^2(2x)+3cos(2x) | | 3x=2y+z | | 4y-7+3y-9=4y+(-7)+3y+9 | | 21s+3=126 | | 5(x+2)-4(x+1)=0 | | 4x+11y=450 | | 6x+(-5)=3x+(-29) | | 4(x+21)-3(-x+7)=-28 | | 6x+(-5)=3x(-29) | | 4l+3=50 | | 4l+3=20 | | 4w+9x-12y+6w+3x+7y= | | 2x+2y=4x-3 | | 4(x+8)+2(-x+2)=4 | | 77x=35 | | .3t+0.7(t-.2)=1.12 | | (2/5)^(3/1) | | 15-3m=3m+81 | | 282x=383372727383 | | 9-4x=-53 | | 4y-5+4y-8=4y+(-5)+4y | | 2(x+10)+3(x+20)=-15 | | 8(m-3)-7(m+4)=-52 | | 14x=21x^2 | | 20+(140-x)+x+y= | | xsquared+1=145 | | 7400-1/2x | | 1/2x1/6=1/4x-1/4 | | 3y+15x=7 | | 7400-1/2px | | 3(5x+11)=4(x+44) |

Equations solver categories